Medical ethics education: an interdisciplinary and social theoretical perspective - Emmerich, Nathan (SpringerBriefs in Ethics, 2013)
There is a diversity of 'ethical practices' within medicine as an institutionalised profession as well as a need for ethical specialists both in practice as well as in institutionalised roles. This Brief offers a social perspective on medical ethics education. It discusses a range of concepts relevant to educational theory and thus provides a basic illumination of the subject. Recent research in the sociology of medical education and the social theory of Pierre Bourdieu are covered. In the end, the themes of Bourdieuan Social Theory, socio-cultural apprenticeships and the 'characterological turn' in medical education are draw together the context of medical ethics education.